IMPROVING STUDENT LEARNING OUTCOMES WITH THE TARL APPROACH TO SCIENCE SUBJECTS IN ELEMENTARY SCHOOLS - Isna Rahmawati; Theresia Ani Widyastuti; Eka Agus Sentosa , dkk; Diah Ayu Wulandari; Dwi Nugraini (Universitas Islam Negeri Mataram, 2025)
This project uses the Teaching at The Right Level (TaRL) methodology to enhance students' learning outcomes in Natural and Social Sciences (IPAS) courses. Classroom Action Research (CAR), the research methodology employed, is divided into two cycles, each comprising diagnostic testing, student categorization according to comprehension level, and the implementation of suitable learning techniques. The study's findings suggest that using the TaRL technique can significantly enhance students' learning outcomes. The percentage of students who completed the classical portion rose from 30.76% in the pre-cycle to 84.61% in cycle II, while the average student score rose from 60.92 in cycle I to 78.54 in cycle II. This method enhances learning outcomes and positively affects student motivation and engagement. As a result, the TaRL approach may be a valuable tactic for addressing variations in students' comprehension levels and fostering more inclusive, individual-centered learning.